High-Efficiency Sky Blue-To-Green Fluorescent Emitters Based on 3-Pyridinecarbonitrile Derivatives - Masuda, Yuki; Sasabe, Hisahiro; Arai, Hiroki; Onuma, Natsuki; Kido, Junji (Frontiers in Chemistry, 2019)
The pyridinecarbonitrile derivative is well known as an acceptor unit in fluorescent materials. However, its use in thermally activated delayed fluorescent (TADF) emitters is very limited compared with its benzenecarbonitrile counterparts. Very recently, we developed a series of 4-pyridinecarbonitrile, so-called isonicotinonitrile derivatives, as a highly efficient sky blue-to-green TADF emitters realizing low-drive-voltage organic light-emitting devices (OLEDs). In this work, we contributed new design and development for three 3-pyridinecarbonitrile-based TADF emitters named 2AcNN, 2PXZNN, and 5PXZNN. Among these emitters, a sky blue emitter, 2AcNN, showed a maximum external quantum efficiency (ηext,max) of 12% with CIE (0.19, 0.36). While green emitters, 5PXZNN and 2PXZNN, realized highly efficient TADF OLEDs with a ηext,max of 16–20%. Introduction of electron-donor moiety into the 2-position of 3-pyridinecarbonitrile contributes a larger overlapping of frontier molecular orbitals (FMOs) and stronger intramolecular charge transfer (ICT) interaction generating efficient TADF emitters.